Connecting food with planning profession: a review paper on the development and evolution of urban food planning, education and research - Chang, Hsiu Tzu Betty; Lee, Chi Yun (AESOP, 2017)
The food system has been noticed by planning profession since the World Health Organization launched the Healthy Cities movement in the1980s. As the result, countries gradually started to focus on the health, agricultural and urban food security issue and make efforts to create healthier and more liveable cities ever since. Food system has been regarded as production and consumption of food in general and could be divided into the policy and planning dimensions. Food policies are about agriculture, economic development, logistics and education can cooperate with each other in policy actions or how non-governmental organisations, farmers and other different stakeholders can work with the government. The spatial planning of urban food is related to how we can improve the access for people to get the healthy food and how to implement the sustainable urban food planning. In addition, urban design concerning the application of productive landscape and other tools are also parts of spatial interventions to urban agriculture and food city. Although food planning has gradually been discussed in recent years, there has been a lack of systematic review about this planning trend. In this paper, we reviewed the literature related to the subject of urban food planning since 1980. Through analysing articles in planning related journals, we created the literature maps and descriptive statistics that document the current development of food planning literature and organise them by the definition, themes, history, typology, evolution and future direction of food in connection with the planning research, practice and education. We wish to contribute to this emerging planning and design paradigm that concerning about food, public health, sustainability and the new rural-urban relationship.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017